Design And Implementation Of An Accounting Information System At Kedai Kopi Simpang Empat - Meily Juliani; Saphira Evani (ConCEPt - Conference on Community Engagement Project, 2023)
This project intends to design an adequate accounting system that is easy to understand to solve the problem encountered by Kedai Kopi Simpang Empat in recording and reporting financial activity. This problem arises as the business struggles to record the ingoing and outgoing cash flow manually hence increasing the occurrence of recording errors. In addition, the business also faces difficulty in generating financial reports resulting in delays or wrong decision-making for the future growth of the business. The methods used in compiling data are interviews, observation and documentation. The implementation result of the system proves that there is an improvement in the effectiveness and efficiency of the financial recording and reporting activity as the system can assist its day-to-day transactions and convert them into analysable financial reports. As the system’s design is relatively simple, it is recommended that future researchers improve the design and add more features to create a more user-friendly system for the users.